The influence of dead space in blood sampling needle on FVIII level and pharmacokinetic profiles in children with hemophilia - Yingzi Zhen; Di Ai; Kun Huang; Gang Li; Zhenping Chen; Runhui Wu (Hematology)
Objective To investigate the influence of the dead space in disposable blood sampling needle on activated partial thromboplastin time (APTT), FVIII level and pharmacokinetic (PK) profiles in children with hemophilia.Methods Children (<18 years) with severe hemophilia A were enrolled. After three days’ washout-period, blood samples were collected at pre-dose, 1 h, 3 h, 9 h, 24 h and 48 h post-infusion. At each timepoint, two 2 mL vacuum tubes with 3.2% trisodium citrate were used. The first tube was signed as ‘non-standard’ (NS) and the second tube was signed as ‘standard’ (S). FVIII activities were evaluated by one-stage assay. WAPPS-Hemo was used to generate PK profiles like half-life time (t1/2), clearance (CL), trough level and time to 1, 2 and 5IU/dL after a dose of 50 ± 10IU/dL. The FVIII activities at 9 h and 24 h post-infusion were put into WAPPS and thus brought four combinations by true or biased FVIII level that used.Result Compared with standard-collected blood samples, prolonged APTT results (P-values < 0.01) and decreased FVIII activity (P-values < 0.05) were revealed in those non-standard blood samples. The corresponding bias was in positive relation to both APTT-S (r = 0.44, P < 0.0001) and FVIII-S level(r = 0.68, P < 0.001). The FVIII bias percentage got larger as FVIII-S level reduced (r = −0.24, P < 0.01). During the four combinations of FVIII activity at 9 h and 24 h, statistically longer t1/2, lower CL and longer time to 1, 2 or 5IU/dL were observed in 9H-S&24H-S group and 9H-NS&24H-S group.Conclusion While using vacuum tubes for clotting indicators and PK profiles, the dead space of blood sampling needle should be eliminated in advance.